3D Cell‐Printing: 3D Cell Printing of Functional Skeletal Muscle Constructs Using Skeletal Muscle‐Derived Bioink (Adv. Healthcare Mater. 20/2016). Issue 20 (26th October 2016) - Choi, Yeong‐Jin; Kim, Taek Gyoung; Jeong, Jonghyeon; Yi, Hee‐Gyeong; Park, Ji Won; Hwang, Woonbong; Cho, Dong‐Woo
Abstract : On page 2636, Dong‐Woo Cho and co‐workers introduce a skeletal muscle‐derived bioink with 3D cell printing technology that facilitates the fabrication of 3D functional muscle constructs. 3D cell printing technology can generate various types of constructs and cellular alignments in a controlled manner. The bioink retains the major ECM molecules that provide a microenvironment similar to that of native muscle and induce myogenesis in 3D cell‐printed muscle constructs.